(untitled) (Journal of Dhaka Medical College, 2010)
Through and through orbitocranial penetrating injury by in situ teta is extremely rare. We managed such a case in Dhaka Medical college hospital with many limitations. In spite of all possible supports that were available in our set up, patient did not survive. Presentation, investigations, surgical and other supportive management will be highlighted in this case report. Key Words: Orbitocranial injury; penetrating injury; teta. DOI: 10.3329/jdmc.v18i2.6285 J Dhaka Med Coll. 2009; 18(2) : 185-187